2022
DOI: 10.1038/s41593-022-01193-4
|View full text |Cite|
|
Sign up to set email alerts
|

Astrocytes mediate long-lasting synaptic regulation of ventral tegmental area dopamine neurons

Abstract: The plasticity of glutamatergic transmission in the Ventral Tegmental Area (VTA) represents a fundamental mechanism in the modulation of dopamine neuron burst firing and the phasic dopamine release at VTA target regions. These processes encode basic behavioral responses, including locomotor activity, learning and motivated-behaviors. Here we describe a hitherto unidentified mechanism of long-lasting potentiation of glutamatergic synapses on DA neurons. We found that VTA astrocytes respond to dopamine neuron bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Provided the wealth of evidence indicating neuronal ABHD6 controls canonical endocannabinoid signalling function 3,6 , our study focused on neuronal ABHD6 function. However, the potential role of ABHD6 in glial-derived synthesis or termination of 2-AG signaling 138,139 and glial CB1R signaling 64,140,141 represents an interesting area for future investigation considering prominent non-neuronal ABHD6 expression 51 . Unpaired t-test (5C, 5F, 5H, 5J, 5L, 5N), two-way ANOVA group x time interaction with Sidak's post hoc correction (5D, 5G, 5I, 5K), two-way ANOVA group main effect (5E, 5M).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Provided the wealth of evidence indicating neuronal ABHD6 controls canonical endocannabinoid signalling function 3,6 , our study focused on neuronal ABHD6 function. However, the potential role of ABHD6 in glial-derived synthesis or termination of 2-AG signaling 138,139 and glial CB1R signaling 64,140,141 represents an interesting area for future investigation considering prominent non-neuronal ABHD6 expression 51 . Unpaired t-test (5C, 5F, 5H, 5J, 5L, 5N), two-way ANOVA group x time interaction with Sidak's post hoc correction (5D, 5G, 5I, 5K), two-way ANOVA group main effect (5E, 5M).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Previous studies have reported astrocyte [Ca 2+ ] i activity in somas (Corkrum et al, 2020;Fischer et al, 2020;Jennings et al, 2016;Pittolo et al, 2022;Requie et al, 2022) and large processes or microprocesses (Pittolo et al, 2022;Requie et al, 2022) in response to DA. By refining our experimental procedure (gradual reduction of DA quantity) and analysis (activity-based analytical framework), we found that spinal astrocyte [Ca 2+ ] i activity started in the endfeet.…”
Section: Pattern Of Astrocyte [Ca 2+ ] I Activitymentioning
confidence: 99%
“…More recently, another catecholamine, dopamine (DA), has also been shown to activate astrocytes. In the nucleus accumbens, the hippocampus, and the ventral tegmental area, DA acting on D 1 or D 2 receptors induces an increase in [Ca 2+ ] i in astrocytes (Corkrum et al, 2020; Jennings et al, 2016; Requie et al, 2022), while in the ventral midbrain and in the hippocampus, it induces a [Ca 2+ ] i decrease mediated by D 2 receptors (Jennings et al, 2016; Xin et al, 2019). Interestingly, DA also triggers [Ca 2+ ] i activity in astrocytes from the prefrontal cortex, but this response is mediated by the activation of α 1 ‐adrenergic receptors (Pittolo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes, a type of multifunctional cell and active communication partners, 10 form an integral part of the blood−brain barrier, contributing to protecting the brain from toxic metabolites and peripheral insults. 11 Studies have found that quiescent astrocytes are activated, referred to as reactive astrocytes, in response to a variety of neural damages in the central nervous system. 12 Notably, recent study revealed three distinct states of reactive astrocytes termed as "pan", "A1", and "A2", under various stimuli.…”
Section: Introductionmentioning
confidence: 99%